Boarding schools in the Tuvan ASSR: between Soviet civility and traditional culture - Doptan , Ertine S. (The New Research of Tuva, 2025)
The article presents an analysis of boarding schools in the Tuvan ASSR (1940s–1980s) as social institutions that shaped the collective experience of the Tuvan people during the Soviet period. The author examines boarding schools as part of Soviet colonization policies aimed at assimilating the indigenous peoples of Siberia and Central Asia through the inculcation of socialist values and the promotion of a sedentary lifestyle. The research is based on a qualitative sociological approach, including the collection of oral histories and biographical interviews with former boarding school students from different districts of Tuva, as well as an examination of archival materials and publications in regional media. The author explores the structure of boarding schools, the features of the disciplinary regime, living conditions, food and clothing, as well as the mechanisms of introducing and displacing elements of traditional culture and language. It was found that despite strict control and ideological influence, boarding schools preserved a hidden practice of traditional culture, while attitudes toward Soviet innovations were temporally and situationally variable: positive memories coexist with narratives of trauma and longing for home. The contradictory role of boarding schools is revealed: on the one hand, they functioned as instruments of socialization and provision of benefits; on the other, they became sources of collective trauma associated with the disruption of family ties and the loss of part of ethnocultural identity. In conclusion, the author emphasizes the uniqueness of the Tuvan boarding school experience as a hybrid form of socialization, combining Soviet and local elements.